2010
DOI: 10.1039/c000091d
|View full text |Cite
|
Sign up to set email alerts
|

Advances in NMR-based biofluid analysis and metabolite profiling

Abstract: Significant improvements in NMR technology and methods have propelled NMR studies to play an important role in a rapidly expanding number of applications involving the profiling of metabolites in biofluids. This review discusses recent technical advances in NMR spectroscopy based metabolite profiling methods, data processing and analysis over the last three years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 134 publications
(224 reference statements)
0
96
0
4
Order By: Relevance
“…Versatile analytical techniques mainly based on Nuclear Magnetic Resonance spectroscopy (NMR) and Mass Spectrometry (MS) allow the analysis of various samples from bio-fluids such as serum or urine, and exhaled breath condensate, to intact cells or tissues [12][13][14][15]. Meanwhile, metabolomic approaches have already found promising applications in different fields from toxicology [16], functional genomics [11,17] , to oncology [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Versatile analytical techniques mainly based on Nuclear Magnetic Resonance spectroscopy (NMR) and Mass Spectrometry (MS) allow the analysis of various samples from bio-fluids such as serum or urine, and exhaled breath condensate, to intact cells or tissues [12][13][14][15]. Meanwhile, metabolomic approaches have already found promising applications in different fields from toxicology [16], functional genomics [11,17] , to oncology [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, only few NMR studies of this type are reported [9,10]. The main reason is probably the large number of patients required for this kind of study considering the high individual and inter-individual variability of metabolic profiles found in biological fluids.…”
Section: Introductionmentioning
confidence: 94%
“…Mass spectrometry (MS) and nuclear magnetic resonance (NMR) are the two analytical platforms most predominantly used in metabolomics. NMR permits the analysis of complex mixtures of metabolites with little or no sample preparation in a rapid and non-destructive way (Zhang, Nagana-Gowda, Ye, & Raftery, 2010) and has been largely applied in metabolomics (Zhang & Powers, 2012). Although NMR spectra are very informative, low sensitivity and high data complexity limit quantitative profiling to less than100 compounds in most biological samples (Bain et al, 2009).…”
Section: Metabolomics and Neurodegenerative Disordersmentioning
confidence: 99%